DIALOGUE, ECHOES AND CRANNIES: THE SCIENTIFIC COMMUNICATION IN ACADEMIC AMBIT - Castillo Vargas, Andrés (2015)
This paper is a theoretical reflection on the nature and importance of the processes ofscientific communication within the academic world. The communication of science isa process used by researchers to present their findings; it may be aimed at specializedacademic or public peers, or wider and heterogeneous public. Communicating sciencecan be done directly, by who investigates or by mediation of professionals in journalism,who do reach the public to the knowledge generated in academic areas. Understandingthe process of communicating gear science is crucial to create effective strategies for theirdevelopment and visualization as a specific objective of the process of scientific research.